COLLABORATIONISM IN MODERN UKRAINE AS A CRIMINAL-LEGAL PROBLEM - Lykhova, Sofiia; Komanetska, Viktoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: a scientific review in the criminal and legal aspect of collaborationism as an actual socially dangerous phenomenon that arose in Ukraine and continues to exist as a result of the occupation activities of the troops of the aggressor state. The study of the criminal legal problems of collaborationism aims at its deeper study and development of methods for overcoming legal gaps and, in the rest, obtaining new applied and effective scientific achievements. Research methods: this scientific work was created by using general scientific methods of cognition: comparative-legal, formal, analytical, system-structural and other methods. Results: the authors of this study determined that clarifying the essence of the problem of collaborationism will lead to overcoming the gaps in criminal law in this area. Discussion: the discussion of this study is devoted to the peculiarities of the criminal-legal essence of the problem of collaborationism, its legal regulation in Criminal Code of Ukraine, and the determination of the strengths and weaknesses of the new draft law aimed at regulating the investigated issue. One of these problems is the spread of collaborative activities in the temporarily occupied and alienated territories of Ukraine, which is caused by the use of a wide range of hybrid warfare methods by the Russian authorities. Such activities of the Russian Federation led to the fact that Ukraine temporarily lost part of its territories, starting in 2014, and some of the territorial units of Ukraine are still under the occupation authorities (the Autonomous Republic of Crimea, regions of Donetsk and Luhansk regions, regions of Kherson and Zaporizhzhia regions). At the same time, one of the most important prerequisites for the temporary consolidation of the occupying power in the above-mentioned regions of Ukraine is the active conduct of collaborative activities by persons who support the order of the enemy.